Glued linear connection on surface of the projective space - K.V. Bashashina (Дифференциальная геометрия многообразий фигур, 2020)
We consider a surface as a variety of centered planes in a multidimensional projective space. A fiber bundle of the linear coframes appears over this manifold. It is important to emphasize the fiber bundle is not the principal bundle. We called it a glued bundle of the linear coframes. A connection is set by the Laptev — Lumiste method in the fiber bundle. The ifferential equations of the connection object components have been found. This leads to a space of the glued linear connection. The expressions for a curvature object of the given connection are found in the paper. The theorem is proved that the curvature object is a tensor. A condition is found under which the space of the glued linear connection turns into the space of Cartan projective connection. The study uses the Cartan — Laptev method, which is based on calculating external differential forms. Moreover, all considerations in the article have a local manner.